A pilot study evaluating the effects of concussion on the ability to form cognitive maps for spatial orientation in adolescent hockey players. (2nd July 2020) - McFarlane, Liam Heath; Burles, Ford; Yeates, Keith Owen; Schneider, Kathryn; Iaria, Giuseppe
ABSTRACT: Objective: In this pilot study, we investigated the impact of a sport-related concussion (SRC) on the ability to form cognitive maps, mental representations of the environment that are critical for spatial orientation and navigation. Participants: We recruited 18 adolescent hockey players suffering from a SRC, and 19 age, sex and handedness-matched hockey players with no history of concussion. Main measure: We asked participants to perform the Spatial Configuration Task (SCT), a computerized tool used to quantitatively measure the ability of the individuals to form cognitive maps. Results: We found that athletes with a concussion performed significantly worse than controls on the SCT ( F (1, 34) = 5.82, p =.021, d ˆ = −0.72), confirming a negative effect of a SRC on the ability to form cognitive maps. We found no significant difference between groups in average response time, and no significant correlation between participants' performance at the SCT and reported symptoms of concussion as rated on the Sport Concussion Assessment Tool (SCAT5). Conclusions: Consistent with the integrity of extended neural networks required for effective spatial orientation and navigation, the findings of our pilot study provide preliminary evidence suggesting that a SRC may affect the ability to familiarize with a spatial surrounding and orient within it.